KETERAMPILAN PROSES SAINS PADA KONSEP EKOSISTEM MELALUI OUTDOOR LEARNING DAN POST TO POST DI SMA NEGERI 1 SUNGAI KAKAP - kurnia tiara aulia (Pedagogi Hayati, 2018)
This research motivated by student’s science proses skills which is low and one of them influenced by the teaching methods provided. A comparison of science process skills on different application of learning methods can determine appropriate methods for improving students process skills. This research purposes is, 1) to know the difference of students science process skills which is taught using outdoor learning and post to post, 2) to know which learning methods is the most affective to increase students science process skills in both of cognitive and psychomotor aspect. This research uses Quasi Experimental with Nonequivalent Control Group Design. The Sampling technique used purposice sampling. Data collection techniques uses measurement techniques for the cognitive science process skills and observation for the psychomotor science process skills. The gain value of reasearch result cognitive aspect in outdoor learning class is 35,39, post to post is 31,41and the test result of U-Mann whitney is 0,022 . The average value of psychomotor science process skills in outdoor learning class is 82,05, post to post class is 85,82 and the test result of U-Mann whitney is 0,006. The conclusion in this research there is a difference of cognitive science process skills between outdoor learning and post to post. the most effective of learning method for improving the cognitive science process skills is outdoor learning, and to improving the psychomotor science process skills is post to post.